WHEN MEN ARE VICTIMS: POWER, HEGEMONIC MASCULINITY, AND THE EPISTEMIC LIMITS OF JUSTICE IN INDONESIAN SEXUAL VIOLENCE LAW - Nugroho, Mohammad Shandy; Hardiyanti, Marzellina; Mahoro, Jean Claude Geofrey (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
This study critically examines the treatment of sexual violence against men within the framework of Indonesian criminal law, highlighting the persistent influence of hegemonic masculinity on legal culture and courtroom practices. Historically, Indonesian law has constructed sexual violence through a gendered lens that positions men as active perpetrators and women as passive victims, thereby marginalising male victims and limiting societal and institutional recognition. Despite normative reforms, including the Sexual Violence Criminal Law and the New Criminal Code, which adopt gender-neutral definitions and acknowledge coercion, power dynamics, and non-physical forms of violence, the implementation of these laws remains constrained by patriarchal legal culture. Using a Foucauldian feminist approach, the study demonstrates that courts often privilege physical evidence and linear narratives of trauma, thereby subordinating the psychological and relational dimensions of male victimisation. Empirical cases, including sexual violence against a male student in Batu City and the victimisation of 43 boys in a religious educational institution in Agam Regency, illustrate how judicial masculinity operates to standardise rationality, depoliticise power relations, and symbolically protect patriarchal norms. Male victims are compelled to negotiate their masculinity, conform to societal expectations, and substantiate trauma within a framework biased toward physical proof. The study further contextualises these dynamics internationally, comparing the recognition of male rape in jurisdictions such as the United Kingdom, the United States, and the International Criminal Court, underscoring the global persistence of gendered assumptions that impede legal acknowledgment and social support for male victims. The analysis concludes that achieving substantive gender justice requires a transformation of the epistemology of legal practice: courts must reconceptualise sexual violence as a mechanism of domination and social control rather than an anomaly, and recognise male vulnerability without pathologisation. Only through integrating legal cultural analysis, trauma-informed evidence evaluation, and awareness of hegemonic masculinity can the law substantively protect male victims and dismantle the structural biases that perpetuate the marginalisation of men within sexual violence discourse.